Philosophical perspectives on depiction - Abell, Catharine; Bantinaki, Katerina (Oxford : Oxford University Press, 2010)
This volume offers to set the agenda for the philosophy of depiction. It addresses a wide range of philosophical issues concerning the nature and value of depiction, the role of our perceptual processes in interpreting pictures and the role of depiction in everyday communication.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Image (Philosophy)